Social loafing a meta-analytic review and theoretical integration - Karau, Steven; Williams, Kipling D. (The American Psychological Association Inc., 1993)
Social loafing is the tendency for individuals to expend less effort when working collectively than when working individually. A meta-analysis of 78 studies demonstrates that social loafing is robust and generalizes across tasks and S populations. A large number of variables were found to moderate social loafing. Evaluation potential, expectations of co-worker performance, task meaningfulness, and culture had especially strong influence. These findings are interpreted in the light of a collective effort model that integrates elements of expectancy-value, social identity, and self-validation theories.